Agronomic and physiological response of giant reed (Arundo donax L.) to soil salinity - Di Mola, Ida; Guida, Gianpiero; Mistretta, Carmela; Giorio, Pasquale; Albrizio, Rossella; Visconti, Donato; Fagnano, Massimo; Mori, Mauro (Italian Journal of Agronomy, 2018)
The soil salinity increase in the Mediterranean basin is one of the consequences of the climate change. The aim of this study was to evaluate the adaptability of giant reed (Arundo donax L.) to salinity, in conditions of higher temperatures, in order to hypothesise the future use of giant reed under these conditions. The trial was carried out in pots under a permanent metal structure, open on the sides and with a clear PE on the top. Four levels of soil salinity in the range 3.3-15.5 dS m–1 were imposed. The stem number of the most stressed treatment was about 45% lower than the control and also the stem height was lower than in all other treatments. The green and yellow leaf number decreased as the soil salinity increased, and their sum was significantly lower in the two most stressed treatments. Osmotic potential of the leaf sap was not affected by salinity. Leaf water potential and stomatal conduc- conductance in the saline treatments were lower than in the control. tance Assimilation rate showed similar pattern of stomatal conductance. Intrinsic WUE remained almost stable until July and increased during August under the most stressful conditions. PSII photochemistry was not affected by soil salinity. Biomass yield was not different from the control until to soil ECe 12.0 dS m–1: only the most stressed treatment (15.5 dS m–1) caused yield losses (50%). Tolerance threshold to salinity was 11.2 dS m–1 and the relative yield losses were 11.6% per dS m–1.